An inpatient Healthy Living Group. Issue 2 (2014) - ,; ,; ,
Abstract : Purpose – The purpose of this paper is to evaluate the usefulness of a Healthy Living Group (HLG) for individuals with learning disabilities and mental health problems in an inpatient setting.Design/methodology/approach – Seven sessions were developed. Each session focussed on a different aspect of healthy living, and used psychoeducation and practical skill building to enable individuals to create personalized healthy living plans. Quantitative post‐intervention measures and a qualitative focus group were used to determine group participants' learning and enjoyment.Findings – Principles about healthy living were successfully taught in an enjoyable way to individuals with learning disabilities. Factors that enhanced learning and those that created barriers to developing healthy living plans are explored.Practical implications – Individuals with learning disabilities and mental health problems can be supported to develop personalized healthy living plans. Recommendations for further adaptations to the group structure are made, in order to enable others to run successful groups.Originality/value – The HLG is the first of its kind to be developed for individuals with learning disabilities. Acknowledgements : The authors would like to thank staff and residents for their participation and support. This case study was carried out by the first two authors and was supervised by the third author in the context of placement contracts. There was no external funding.